2017
DOI: 10.1038/srep40900
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological and anatomical traits of plant functional types in temperate grasslands along a large-scale aridity gradient in northeastern China

Abstract: At the species level, plants can respond to climate changes by changing their leaf traits; however, there is scant information regarding the responses of morphological, physiological and anatomical traits of plant functional types (PFTs) to aridity. Herein, the leaf traits of five PFTs representing 17 plant species in temperate grasslands were examined along a large-scale aridity gradient in northeastern China. The results show that leaf thickness in shrubs, perennial grasses and forbs increased with heightene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 55 publications
3
37
0
1
Order By: Relevance
“…This result is consistent with the findings reported in previous studies (Chapolagh Paridari et al, 2013;Gratani et al, 2012). Also, this result is consistent with the findings of Guo et al (2017), which showed an opposite pattern in SDW and RWC values in the shrubs along elevation gradients. Poulos et al (2012) showed that RWC changed more within elevation gradients for four pine species.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the findings reported in previous studies (Chapolagh Paridari et al, 2013;Gratani et al, 2012). Also, this result is consistent with the findings of Guo et al (2017), which showed an opposite pattern in SDW and RWC values in the shrubs along elevation gradients. Poulos et al (2012) showed that RWC changed more within elevation gradients for four pine species.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, these traits appear to be good proxies for drought tolerance in these grasslands. Leaf thickness can influence leaf N•area −1 and water use efficiency (Wright, Reich, & Westoby, 2003), and increases with increasing aridity (Guo, Ma, Yuan, & Wang, 2017;Niinemets, 2001). High leaf pubescence increases reflectance of solar radiation, minimizing the need for transpirational cooling; it can also increase resistance of the leaf boundary layer to diffusion, thereby minimizing water vapour movement away from the leaf surface (Skelton, Midgley, Nyaga, Johnson, & Cramer, 2012).…”
Section: Trait Selectionmentioning
confidence: 99%
“…Plant functional traits (PFTs) are commonly used to identify species' differences in growth, allocation, and competition in relation to environmental effects to reflect plant economics (Grime, 1979;Edwards et al, 2007;Guo et al, 2017;Volaire, 2018). PFTs represent morphological and physiological adaptations that often predict plant responses to biotic (competition, herbivory, etc.…”
Section: Plant Functional Traits Reflect Ecophysiological Processesmentioning
confidence: 99%